1997
DOI: 10.1007/s004300050049
|View full text |Cite
|
Sign up to set email alerts
|

Antirotaviral activity of milk proteins: lactoferrin prevents rotavirus infection in the enterocyte-like cell line HT-29

Abstract: Different milk proteins were analyzed for their inhibitory effect on either rotavirus-mediated agglutination of human erythrocytes or rotavirus infection of the human enterocyte-like cell line HT-29. Proteins investigated were alpha-lactalbumin, beta-lactoglobulin, apo-lactoferrin, and Fe(3+)-lactoferrin, and their antiviral action was compared with the activity of mucin, a milk glycoprotein known to affect rotavirus infection. Results obtained demonstrated that beta-lactoglobulin, apo- and Fe(3+)-lactoferrin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(102 citation statements)
references
References 36 publications
(43 reference statements)
3
95
2
Order By: Relevance
“…Multiple studies have shown that apo-lactoferrin (iron-depleted lactoferrin) and hololactoferrin (iron-saturated lactoferrin) from bovine milk suppress rotavirus attachment and replication in vitro [12][13][14]; however, not all investigators have been able to confirm an effect [15]. The effect of lactoferrin on other viral enteritis organisms has not been fully evaluated.…”
Section: Effect Of Lactoferrin On Enteric Virusesmentioning
confidence: 99%
“…Multiple studies have shown that apo-lactoferrin (iron-depleted lactoferrin) and hololactoferrin (iron-saturated lactoferrin) from bovine milk suppress rotavirus attachment and replication in vitro [12][13][14]; however, not all investigators have been able to confirm an effect [15]. The effect of lactoferrin on other viral enteritis organisms has not been fully evaluated.…”
Section: Effect Of Lactoferrin On Enteric Virusesmentioning
confidence: 99%
“…This occurs by neutralisation of the viruses with virus-speci®c secretory immunoglobulin A (sIgA) [15]. However, lactoferrin of bovine origin can inhibit growth of simian rotavirus SA11 [16], as can ganglioside GM1 [4]. Either bovine or human milk lactoferrin can interfere with growth of poliovirus type 1 [17].…”
Section: Introductionmentioning
confidence: 99%
“…Binding to viral particles to prevent both rotavirus haemagglutination and viral binding to receptors on susceptible cells [30,40] human lactadherin Binding to structural protein of rotavirus and inhibits virus replication [37,38] Virus Protein or peptide Model of antiviral function Reference high molecular glycoprotein (e.g. mucin)…”
Section: Hepatitis B Virus Iron-or Zinc-saturated Lactoferrinmentioning
confidence: 99%
“…Most of the whey proteins have been demonstrated to effectively prevent viral infection. For example, milk derived proteins including -lactalbumin, -lactoglobulin, apo-lactoferrin (iron free), and homo-lactoferrin (Fe 3+ carrying), were able to inhibit rotavirus attachment to cellular receptors by binding to the viral particle [30]. Among these proteins, apo-lactoferrin was proven to be the most active.…”
Section: Protein Composition Of Milk and Their Antiviral Activitymentioning
confidence: 99%
See 1 more Smart Citation